2019
DOI: 10.1002/cbm.2110
|View full text |Cite
|
Sign up to set email alerts
|

Does emotion matter? The role of alexithymia in violent recidivism: A systematic literature review

Abstract: Background Several variables have been evidenced for their association with violent reoffending. Resultant interventions have been suggested, yet the rate of recidivism remains high. Alexithymia, characterised by deficits in emotion processing and verbal expression, might interact with these other risk factors to affect outcomes. Aim Our goal was to examine the role of alexithymia as a possible moderator of risk factors for violent offender recidivism. Our hypothesis was that, albeit with other risk factors, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 79 publications
3
27
0
Order By: Relevance
“…Additionally, it is necessary to keep in mind that our data also revealed that the IPVAW perpetrators presented an average score which was higher than the cut-off score ( > 61) on TAS-20 which indicated the existence of a marked presence of alexithymia in this group. These results were in line with previous studies in this field of research [6,7,9,10,11]. We also demonstrated the robust association of alexithymia with dropout and risk of reoffending.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, it is necessary to keep in mind that our data also revealed that the IPVAW perpetrators presented an average score which was higher than the cut-off score ( > 61) on TAS-20 which indicated the existence of a marked presence of alexithymia in this group. These results were in line with previous studies in this field of research [6,7,9,10,11]. We also demonstrated the robust association of alexithymia with dropout and risk of reoffending.…”
Section: Discussionsupporting
confidence: 93%
“…The authors concluded that alexithymic traits were associated with dysexecutive symptoms, high impulsivity, and poor empathic skills [9]. Moreover, these symptoms could be worse if individuals present other risk factors for violence, such as drug misuse [10,11]. This might explain the tendency of these individuals to experience violent outbursts when they cope with stress.…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified multiple risk factors for aggressive and violent behavior related to schizophrenia (23)(24)(25). Deficits in affective processing are suggested as one of the main precursors to violent behavior (26). This type of difficulty is also one of the key features of schizophrenia as defined by the DSM [DSM-5, (27)] and has been identified in various studies [e.g., (6,28,29)].…”
Section: Perception Of Social Cues In Schizophrenia and Violent Behaviormentioning
confidence: 99%
“…spoken with a stern, serious prosody. As violent offenders may display a "hostile attribution bias, " a tendency to view neutral expressions and behaviors as hostile [(82); for a review, see (26)], failing to inhibit the (negative) prosodic cues may lead to inappropriate social reactions for forensic patients with schizophrenia [see also (83)]. Indeed, poor executive functioning (e.g., inhibition) has also been associated with the risk of aggressive-behavior recidivism in schizophrenic patients (72).…”
Section: Larger Failures Of Selective Attention and Prosodic Dominancementioning
confidence: 99%
“…High levels are an important risk factor for psychiatric disorders characterised by emotional dysregulation (Taylor et al, 1999). Interest in the construct has now extended to forensic settings, with many authors examining alexithymia in offender populations and hypothesising that it might help account for individual differences in criminal behaviour (e.g., Gillespie, Garofalo, & Velotti, 2018; Leshem, van Lieshout, Ben‐David, & Ben‐David, 2019; Payne & Hollin, 2014). Accurate alexithymia assessment is thus important.…”
Section: Introductionmentioning
confidence: 99%